Land Use/Land Cover Changes Using Landsat Imagery in The Upper Citarum Watershed, West Java, Province, Indonesia - Marko, Kuswantoro; Sutjiningsih, Dwita; Kusratmoko, Eko; Adi Prakoso, Widjojo (International Journal of Remote Sensing and Earth Sciences, 2025)
The growth of the population and its activities, especially in the Upper Citarum Watershed (UCW) since the last decade has changed the condition of land that was originally vegetated into built-up land. Uncontrolled land use/land cover (LULC) changes in this watershed will certainly have an ecological and hydrological impact. Moreover, this watershed has a very vital role as a provider of agricultural products and water sources in three large reservoirs on the Java island, i.e. the Saguling, Cirata, and Jatiluhur reservoirs. The existence of these three reservoirs is very reliable in supplying electrical energy for the islands of Java and Bali. This study aims to determine changes in LULC over the last 30 years period (1990-2020). LULC information was obtained from analysis of Landsat imagery in 1990, 2000, 2010 and 2020. Supervised classification methods based on remote sensing and geographic information systems were applied to identify types and changes in LULC, i.e. forests, rice fields, dry farm land, bush-grass, mixed gardens, built-up land, and water bodies. The results showed that during the last 30 years there was a fairly high increase on built-up land (+16.4%), and a fairly high decrease in rice fields (-11.5%). The high increase in the ​​built-up land from 1990 to 2020 is indicated by the high level of land conversion from rice fields and dry land farming. The area of ​​natural LULC such as forest has decreased by -3.2% or about 5,705 ha in the last 30 years. The results of this study are expected to be a reference for the government and environmentalists so that efforts to prevent environmental damage can be carried out early on.